Impact of health education on awareness of HIV/AIDS among school children in rural West Bengal, India - Das, Sulagna; Das, Amiya; Dasgupta, Aparajita (International Journal Of Community Medicine And Public Health, 2016)
Background: HIV/AIDS is recognized as a national priority health issue. Inadequate knowledge, negative attitudes and risky practices are major obstacles to prevent the spread of HIV. With the above view the following study was undertaken to assess the level of awareness regarding HIV/AIDS among school children, to raise their awareness through health education program and to determine if the education program would bring about positive change in the knowledge of high school students. Methods: An interventional study was conducted in a school with all the class IX and X students. A pre-structured questionnaire was used to assess the existing general knowledge on HIV/ AIDS, its mode of transmission, prevention, and some attitude and beliefs. Thereafter educational intervention was done on the same day with the help of power point presentations and black board. One week after the educational intervention, post-test was conducted to know the change in the knowledge. Results: The study revealed that out of 215 students all of the students had heard about HIV/AIDS but only 53.5% knew that AIDS is caused by a virus. As regards to mode of transmission only 34.4% of the students knew about sexual route. There was overall significant change in knowledge (p<0.000) after educational intervention. Univariable logistic regression analyses indicated that before the intervention the students’ level of knowledge about HIV/AIDS was significantly associated with age, grade, father’s occupation and mother’s educational status but when adjusted with other variables father’s occupation lost its significance while the others retained it. Conclusions: Educational programmes with specific intervention are recommended to increase awareness.